2012
DOI: 10.4236/jmmce.2012.111005
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Processing and Characterization of Hydroxyapatite Biomaterials from Different Bio Wastes

Abstract: Development of suitable materials that acts as an interface between the implant and tissues in body system structurally, mechanically and bio functionally is important for the success of tissue engineering. This motivated materials scientists and biologists to find out suitable bioactive materials for the aforementioned purpose. There has been growing interest in developing bioactive synthetic ceramics that could closely mimic natural apatite characteristics. Hydroxyapatite (HAp) has been widely used as a bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 10 publications
7
81
0
11
Order By: Relevance
“…The stretching vibration of the OH À groups corresponds to the signal at $3430 cm À1 (Mondal et al, 2012;Rojas-Mayorga et al, 2013). The asymmetric stretching vibration mode of PO 3À 4 group is given by the signal at $1030 cm À1 , while the P-O bending vibration mode corresponds to the bands at 960 and 605 cm À1 (Mondal et al, 2012;Rojas-Mayorga et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The stretching vibration of the OH À groups corresponds to the signal at $3430 cm À1 (Mondal et al, 2012;Rojas-Mayorga et al, 2013). The asymmetric stretching vibration mode of PO 3À 4 group is given by the signal at $1030 cm À1 , while the P-O bending vibration mode corresponds to the bands at 960 and 605 cm À1 (Mondal et al, 2012;Rojas-Mayorga et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…El fosfato de calcio [Ca10(PO4)6(OH)2] o hidroxiapatita, es especialmente utilizado como material de injerto óseo en aplicaciones médicas y dentales, debido a su gran similitud con la composición natural de los huesos [12], [13]. La HAp es biocompatible y bioactiva, sin embargo presenta malas propiedades mecánicas.…”
Section: Introductionunclassified
“…Other additional benefits can be added, which include their abundance and cheap feedstock. Many studies have reported the mechanism of fish bones thermal decomposition [10][11]. The fish bones were decomposed into calcium oxide at various temperatures before being used as a catalyst in the production of biodiesel from waste cooking oil.…”
Section: Introductionmentioning
confidence: 99%